MINUMAN RUMPUT LAUT DAN MADU DAPAT MENINGKATKAN HAEMOGLOBIN PADA IBU HAMIL - Sri Ayu Arianti; Sri Lestari; Supriyatni Kartadarma (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2021)
Background : Anemia in pregnancy is currently a global problem in Indonesia because it can cause maternal death. The role of iron is very important for pregnant women and fetuses. The risk of anemia in pregnant women can cause postpartum bleeding, prolonged labor and infection during the puerperium. Disorders of fetal development can also be caused by iron deficiency. The importance of efforts to reduce the problem of anemia in pregnant women can be pharmacologically and non pharmacologically. Non-pharmacological treatment can be know as complementary or alternative therapy by giving seaweed and honey drinks. Consumption of foods containing Fe such as seaweed and consumption of food containing Fe absorption aids (Fe enhancers) containing vitamin C can increase hemoglobin levels in pregnant women. Purpose: to determine the effectiveness of seaweed (Eucheuma Spinosum) and honey drinks on increasing haemoglobin levels in pregnant women.Methods : The research using a quasi-experimental research method with one group pre test-post test design. The sampling technique used was the non-probability sampling technique of